Advances in Dynamic Games Applications to Economics, Management Science, Engineering, and Environmental Management - Haurie, Alain; Muto, Shigeo; Petrosjan, Leon A.; Raghavan, T. E. S.; SpringerLink (Online service) (Boston, MA : Birkhäuser Boston, 2006)
The paradigms of dynamic games play an important role in the development of multi-agent models in engineering, economics, and management science. The applicability of their concepts stems from the ability to encompass situations with uncertainty, incomplete information, fluctuating coalition structure, and coupled constraints imposed on the strategies of all the players. This book an outgrowth of the 10th International Symposium on Dynamic Games presents current developments of the theory of dynamic games and its applications to various domains, in particular energy-environment economics and management sciences. The volume uses dynamic game models of various sorts to approach and solve several problems pertaining to pursuit-evasion, marketing, finance, climate and environmental economics, resource exploitation, as well as auditing and tax evasions. In addition, it includes some chapters on cooperative games, which are increasingly drawing dynamic approaches to their classical solutions. The book is thematically organized into six parts: * zero-sum game theory * pursuit-evasion games * games of coalitions * new interpretations of the interdependence between different members of a social group * original applications to energy-environment economics * management science applications This work will serve as a state-of-the art account of recent advances in dynamic game theory and its applications for researchers, practitioners, and graduate students in applied mathematics, engineering, economics, as well as environmental and management sciences.
Zero-Sum Game Theory -- Stochastic Games with Imperfect Monitoring -- Level Sweeping of the Value Function in Linear Differential Games -- Optimal Feedback in a Dynamic Game of Generalized Shortest Path -- Pursuit-Evasion Games -- New Approach to Improve the Accuracy in Delayed Information Pursuit-Evasion Games -- Game Problems for Systems with Fractional Derivatives of Arbitrary Order -- On Two Problems of Group Pursuit -- Games of Coalitions -- Cooperative Stochastic Games -- The Uniqueness of a Reduced Game in a Characterization of the Core in Terms of Consistency -- The Formation of Adaptive Coalitions -- On Assignment Games -- New Concepts of Equilibrium -- The Folk Theorems in the Framework of Evolution and Cooperation -- Stackelberg Problems: Subgame Perfect Equilibria via Tikhonov Regularization -- Extended Self, Game, and Conflict Resolution -- Applications to Energy/Environment Economics -- Game of Timing in Gas Pipeline Projects Competition: Simulation Software and Generalized Equilibrium Solutions -- The Effects of Incomplete Information in Stochastic Common-Stock Harvesting Games -- A Two-Level Differential Game of International Emissions Trading -- A Stochastic Multigeneration Game for Global Climate Change Impact Assessment -- Management Science Applications -- An Impulsive Differential Game Arising in Finance with Interesting Singularities -- Incentives for Retailer Promotion in a Marketing Channel -- Farsighted Behavior Leads to Efficiency in Duopoly Markets -- A Stochastic Game Model of Tax Evasion.
Keywords: Mathematics; Applied mathematics; Engineering mathematics; Game theory; Economics, Mathematical; Computer mathematics; Probabilities; Engineering economics; Engineering economy; Mathematics; Game Theory, Economics, Social and Behav. Sciences; Applications of Mathematics; Computational Mathematics and Numerical Analysis; Quantitative Finance; Engineering Economics, Organization, Logistics, Marketing; Probability Theory and Stochastic Processes; Electronic books